Koleksi bambu Taman Eden 100, Kabupaten Toba Samosir, Sumatera Utara dan perannya dalam taman - Damayanto, I Putu Gede P. (Jurnal Arsitektur Lansekap; Vol.4, No.2, Oktober 2018DO - 10.24843/JAL.2018.v04.i02.p11, 2018)
Bamboo Collections of Taman Eden 100, Toba Samosir Regency, North Sumatra and Its Role in the Garden. The aims of this study are to reveal and describe the collections of bamboo species and its role in Taman Eden 100 landscape. The study was conducted using the explore method, located in Taman Eden 100, Lumban Julu Sub-district, Toba Samosir Regency, North Sumatra. The bamboo herbarium specimens are made to determine the species of each collection of Bamboo of Taman Eden 100. The bamboo specimens are processed and then shipped to the Herbarium Bogoriense (BO) for further identification. The morphology characters also described and to be used in the analysis of the role of each bamboo within Taman Eden 100 landscape. The results showed that Taman Eden 100 has as many as four species of bamboo collections from 10 clumps, namely Bambusa multiplex (bambu cina), Bambusa vulgaris (bambu ampel), Dendrocalamus asper (bambu betung) and Schizostachyum silicatum (bambu suling). Each species of bamboo has different roles in different locations. Some properties of bamboo such as the presence or absence of hairs, culm diameter, culm length, ability in waterlogged or drought conditions and its benefits can be the consideration in choosing the bamboo species and location of planting in a garden.